Manajemen Keamanan Internet Menggunakan Metode Firewall Filtering Untuk Penyaringan Konten Pada Router Mikrotik RB1100 - Sidik Sidik; David Saputra Hasiholan Panjaitan; Priatno Priatno; Esron Rikardo Nainggolan (Computer Science (CO-SCIENCE), 2023)
The existence of security threats and internet abuse is often a problem for companies. Use of a VPN for access to web pages that contain negative and pornographic content which usually contain malware, viruses, trojans and others. This of course will have a detrimental effect on companies whose internet networks are exposed to attacks by malware, viruses or trojans due to employees' habit of accessing web pages that contain negative and pornographic content. To prevent these threats, a method of regulating access and use of the internet network is needed according to its purpose. Content filtering is used to filter sites or web addresses that are not allowed by the company because they are considered to have no direct connection with their field of work. The firewall filtering content method in the Winbox application is one of the methods to achieve the goal of blocking negative and pornographic content that can be accessed by employees during working hours. This research was implemented at PT. Indonesian Mighty Beasts. The results of this study, after the content filtering firewall is implemented, employees cannot access web pages that contain negative and pornographic content and of course are not work related so that the implications for work are more productive, efficient and optimal.